Pengaruh Penambahan Serat Polypropylene pada Kuat Tekan Beton Mutu Tinggi - Andi Yusra; Lissa Opirina; Andrisman Satria; Isma Isma (Universitas Teuku Umar, 2020)
AbstractThe purpose of this study was to determine the effect of adding polypropylene fibers to compressive strength in high quality concrete. The specifications of polypropylene fiber used is a fiber length of 12 mm, fiber diameter of 18 microns and specific gravity of 0.91 gr / cm3. The concrete mixture design method used was trial and error, the quality of the concrete planned is 60 MPa with Water Cement Ratio 0.25 and the use of superplasticizer with a percentage of 2% of the weight of cement. The coarse aggregate to be used is split with a maximum aggregate diameter of 12 mm, and a palm oil clinkers 15% of the weight of cement. The percentage of polypropylene fiber used is 0.5%, 1%, 1.5% of the weight of cement. As a comparison concrete is made without the addition of fiber which is 0%. Concrete compressive strength testing is carried out at 28 days. The total number of test specimens is 24 cylindrical pieces (Ø15 cm, T = 30 cm). The results obtained from the average compressive strength test results at the percentage of 0%, 0.5%, 1% and 1.5% respectively were 57.35 MPa, 55.74 MPa, 54.87 MPa and 50.54 MPa. The optimum conditions are obtained at a percentage of 0.5%. It can be concluded that the addition of polypropylene fibers and palm oil clinkers on high quality concrete can increase the compressive strength of concrete. Keywords— High Strength Concrete, Fibers Concrete, Polypropylene Fibers, Compressive Strength